Cyberattacks, Psychological Distress, and Military Escalation: An Internal Meta-Analysis. Issue 1 (17th January 2023) - Shandler, Ryan; Gross, Michael L; Canetti, Daphna
Abstract: To what extent can cyberattacks wreak havoc and terrorize modern society? Until now, this question has revolved around the potential of cyber operations to cause physical destruction or other material harm. In this paper, we propose a broader interpretation. We submit that assessing cyber-threats through the prism of physical destruction has obscured the human dimension of the threat. Instead, we propose calculating the gravity of cyberattacks by measuring psychological distress . This approach recognizes that even seemingly inconsequential cyberattacks can levy tremendous damage by traumatizing civilians, undermining societal cohesion, and exacerbating cycles of violence. To test whether cyberattacks cause significant individual harm, we employ an internal meta-analysis looking at eighteen studies conducted in three countries over 6 years. Across these studies, we exposed 6, 020 respondents to simulated cyberattacks and conventional attacks. We conclude that cyberattacks can cause high levels of psychological harm—equal even to that caused by conventional political violence and terrorism. This finding overturns a widely accepted view that cyberattacks are a mere irritant at best and a threat to information security at worst. Through this lens, the findings suggest that even nonphysically destructive cyberattacks can trigger consequences that constitute a legally defined armed attack that permits using armed force in self-defense. We conclude by discussing how the onset of psychological distress generates political pressure in support of retaliation and can lead to military escalation.